Differences in growth and physiological and metabolic responses among Canadian native and hybrid willows (Salix spp.) under salinity stress. (21st February 2020) - Huang, Xinyi; Soolanayakanahally, Raju Y; Guy, Robert D; Shunmugam, Arun S K; Mansfield, Shawn D
Abstract: Globally, soil salinization is becoming increasingly prevalent, due to local hydrogeologic phenomena, climate change and anthropogenic activities. This has significantly curtailed current world food production and limits future production potential. In the prairie region of North America, sulfate salts, rather than sodium chloride, are often the predominant cause of soil degradation. In order to amend soil quality, revegetate salt-affected sites and recover economic loss associated with soil salinization, the establishment of short-rotation coppice plantations with willows ( Salix spp.) has been suggested as a possible solution. To screen for the best candidates for such an application, 20 hybrid and 16 native willow genotypes were treated with three different salt conditions for 3 months. The treatments were designed to reflect the salt composition and concentrations on North American prairies. Under moderate salinity treatment (7 dS m −1 ), hybrid willows had better growth, as they established quickly while managing salt transport and mineral nutrition balance. However, native willows showed higher potential for long-term survival under severe salinity treatment (14 dS m −1 ), showing a lower sodium:potassium ratio in roots and better photosynthetic performance. Two native willow genotypes with high osmotic and salinity tolerance indices, specifically LAR-10 and MJW-9, are expected to show superior potential for remediating salt-affected sites. In addition, we observed significantly higher sulfate/sulfur concentrations in both leaf and root tissues in response to the severe salinity treatment, shedding light on the effect of sulfate salinity on sulfate uptake, and potentially sulfur metabolism in plants.